Events and sustainability - Holmes, Kirsten; Hughes, M.; Mair, J.; Carlsen, Jack (Routledge, 2015)
Increasing concerns over climate and environmental change, the global economic and financial crisis and impacts on host communities, audiences, participants and destinations have reinforced the need for more sustainable approaches to events. Sustainability now features as part of the bid process for many mega-events, such as the Olympic Games, as well as significant regional and local events, where the event organisers are required by funding bodies and governments to generate broader outcomes for the locality. This book is the first to offer students a comprehensive introduction to the full range of issues and topics relevant to event sustainability including impacts, operating and policy environments, stimulating urban regeneration and creating lasting legacies, as well as practical knowledge on how to achieve a sustainable event. Taking a holistic approach drawing on multidisciplinary theory it offers insight into the economic, socio-cultural and environmental impacts and how these can be adapted or mitigated. Theory and practice are linked through integrated case studies based on a wide range of event types from mega events to community festivals to show impacts, best practice and how better sustainable practice can be achieved in the future. Learning objectives, discussion questions and further reading suggestions are included to aid understanding and further knowledge; additional resources for lecturers and students including power point slides, video and web links are available online.